A Systematic Review of Green Recovery Model for Forest and Farm Producer Organizations in Vietnam Post-Natural Disasters - Pham, Hong Hai; Le, Kim Lien (European Scientific Journal, ESJ, 2025)
“Green Recovery” is mentioned as a scientific way to revive the economy, solve challenges in health, climate change, biodiversity conservation, and increase the economy’s resilience to other crises that may occur in the future. This paper develops a theoretical framework for green recovery specifically tailored to forest and farm producer organizations (FFPOs) in Vietnam, which are often severely affected by natural disasters, with a specific focus on the case of Typhoon Yagi in Vietnam. Drawing on a systematic review of over 40 peer-reviewed academic studies, the research identifies five foundational pillars of an effective green recovery model: (1) sustainable resource management, (2) green policy integration, (3) technological innovation, (4) community engagement, and (5) circular economy development to minimize environmental impacts. Implementing such a model would not only accelerate post-disaster recovery but also facilitate the transition to a low-carbon, more resilient economy. The paper also provides recommendations for public institutions and international organizations to integrate green recovery into long-term development strategies. In particular, it emphasizes the need to invest in green infrastructure, promote the adoption of sustainable technologies and implement eco-certification programs to enhance the global competitiveness of FFPOs. In conclusion, green recovery is not only a means of mitigating the impact of natural disasters but also a strategic tool for fostering sustainable and inclusive development. Further research is needed to assess the effectiveness of different green recovery strategies within specific socio-economic contexts and to refine policies that support FFPOs.